Juggling School and Work From Home: Results From a Survey on German Families With School-Aged Children During the Early COVID-19 Lockdown - Canales-Romero, Deborah; Hachfeld, Axinja (Frontiers in Psychology, 2022)
As consequence to the coronavirus outbreak, governments around the world imposed drastic mitigation measures such as nationwide lockdowns. These measures included the closures of schools, hence, putting parents into the position of juggling school and work from home. In the present study, we investigated the well-being of parents with school-aged children and its connection to mitigation measures with particular focus on parental roles “caregiver,” “worker,” and “assistant teacher” as stressors. In addition to direct effects, we expected indirect effects on well-being through changes in household dynamics. Data were collected via an online survey (N = 1313, 85.5 % female; 53.2% university degree) conducted during the first wave of school closures in Germany. We observed that during the early COVID-19 pandemic, parental well-being in general was quite positive. Comparing the positive and negative PANAS subscales, parents agreed significantly more with the positive than with the negative items, t(1299) = 28.55, p < .001. Parents also reported an increase in positive family activities during the lockdown, t(1272)= 43.96, p < .001. Although a significant increase in negative household dynamics, such as disputes, was also observed to a lower extent, t(1295)= 7.78, p < .001. Using structural equation modeling, we observed that “homeoffice” was not significantly related to parents’ well-being, but positively affected household dynamics. Taking on the role of “assistant teacher” was negatively related to household dynamics. Additionally, we found a significant direct effect on negative affect for “assistant teacher”. We conclude that parents of school-aged children have mostly been able to establish positive dynamics in their households during the lockdown given the extra time they got to spend with their children by working from home. However, our results identify the role of “assistant teacher” as a potential stressor for parents. Bridging the gap between teachers and parents seems warranted especially if (some) distance-learning continues, in order to avoid long-term consequences for the students.